Integrating Gestalt Theory Concepts in Visual Perception Assessment for Children with Intellectual Disabilities - Muh. Rijal; Mumpuniarti; Muh. Asriadi AM (Journal of Education Reseach and Evaluation, 2024)
Children with intellectual disabilities have difficulties understanding and responding to visual information, which can hinder their development and learning. One of the factors leading to this is the lack of adequate and relevant assessment instruments that reflect the complexity of visual perception processes in children with intellectual disabilities. This study aims to develop a special visual perception assessment for children with intellectual disabilities, utilizing the concepts of Gestalt theory. This study used the Research and Development (R&D) approach and the ADDIE model. The data collection method used was a questionnaire with an instrument in the form of a questionnaire sheet. This instrument was designed and tested for validity by 11 experts and tested on 50 respondents of children with intellectual disabilities. In this study, there were several data analysis techniques, such as content validity being analyzed with Aiken's V Coefficient, while instrument reliability was estimated with Cronbach's Alpha formula. Furthermore, exploratory factor analysis (EFA) was conducted using JASP software to group the questionnaire items into factors based on their dimensions. The results stated that, overall, the instrument was considered valid and reliable for measuring the visual perception ability of children with intellectual disabilities. This study makes an important contribution to the development of assessments that can be applied in education and intervention, improving understanding and support for the visual development of children with intellectual disabilities.